Cessie Transfer of Receivables and its Legal Consequences for the Guarantee of Dependent Rights - Mustofa, Mustofa; Suprapti, Endang (Sebatik, 2024)
The transfer of receivables by cessie is an agreement involving the lender (creditor) and the recipient of the receivables (debtor). This agreement entails the process of transferring the right to claim receivables from the lender to the recipient, usually a bank or other financial institution. The main focus of this study is to analyze the impact of cessie transfers of receivables on the guarantee of security rights (dependent rights). This study examines the legal consequences and changes in the relationship between lenders, debtors, and parties involved in the guarantee of dependent rights. Through a review of legal regulations and case precedents, this study identifies how cessie transfers of receivables can affect the status and priority of dependent rights. The results show that the transfer of receivables through cessie can impact the position and priority of security rights. In some cases, the transfer of receivables can alter the relative position of the debtor in relation to the party holding the dependent rights. Therefore, effective coordination between all parties involved in the transaction is necessary to prevent ambiguities regarding rights and responsibilities. This study provides in-depth insights into the legal complexities associated with cessie transfers of receivables and their implications for security rights. The findings can be utilized by legal practitioners, financial institutions, and parties involved in credit transactions to better understand and manage the risks associated with the transfer of receivables and the protection of security rights.